First record of the presence of Aedes (Phagomyia) cogilli (Edwards, 1922) in Sri Lanka - Jayadas, T.T.P.; Thiruchenthooran, V.; Tharsan, A.; Sivabalakrishnan, K.; Santhirasekaram, S.; Surendran, S.N. (J.Natn.Sci.Foundation Sri Lanka, 2020)
Sri Lanka is known for its biological diversity with a high richness in insect diversity. So far, 159 mosquito species representing 19 genera have been reported. Phagomyia gubernatori is the only species identifi ed under subgenus Phagomyia in Sri Lanka. This study reports the presence of Aedes (Phagomyia) cogilli for the fi rst time in Sri Lanka. During weekly fi eld visits from October to November 2018, larval samples were collected from canals in the Jaff na municipal area in Jaff na District ( N 9° 39’ 32” E 80° 3’ 23” and N 9° 39’ 35” E 80° 3’ 25” ) and reared at the insectary. Emerged adults were identifi ed with available identifi cation keys. DNA was extracted from the individual adults and a portion of the mitochondrial cytochrome c oxidase subunit I (COI) gene was amplifi ed using Polymerase Chain Reaction (PCR). The amplifi ed fragments of four individuals were sequenced in both directions. In addition to morphological confi rmation, the presence of Ae. cogilli was also supported with the DNA sequence of cytochrome c oxidase subunit I. Insecticide susceptibility status of adult mosquitoes to the insecticides Deltamethrin, Permethrin, Malathion, Propoxur, and DDT were performed according to the World Health Organization procedures. The fi ndings showed the presence of Ae. cogilli in Sri Lanka and that it had developed resistance to insecticides, suggesting further investigation on the species.
Keywords: Ae. cogilli; COI; diversity; Sri Lanka